Pengaruh Good Corporate Governance, Pengendalian Internal, dan Whistleblowing System terhadap Pencegahan Fraud - Amelia Destiyana; Fitri Sabiyla Yassarah; Nera Marinda Machdar (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
Any research or scientific paper that aims to substantiate a hypothesis or phenomenon involving relationships between variables must make extensive use of relevant previous research. This article discusses how whistleblower programs, internal controls, and good corporate governance play a role in preventing fraud. This essay is an attempt to provide a foundation for theory about the interaction of factors that may influence future research. First, internal control influences fraud prevention. Second, the whistleblowing mechanism has an influence in preventing fraud. These are the three main conclusions of this research review study.